(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2013)
Cancer is the uncontrolled growth of abnormal cells in the body. It is the most serious disease on which extensive research is being done all over the world. Structure based drug designing offers a computational approach to identify the potential leads which can be developed into a drug. The In-Silico study of the current work aimed at inhibiting the three major targets of cancer by a natural compound Andrographolide from Andrographis paniculata. This exhibited a minimal energy against the targets hence suggesting the stability of the compound. Comparison studies of the compound with the already available anti-cancer drugs and enzyme inhibitors, stated that andrographolide is efficient to act on the targets by exhibiting promising interactions and good scores. This was also found to obey the Lipinski’s Rule of 5 and computed ADMET properties showed the drug likeliness and improved bioavailability. Since it is from a natural source the compound is non toxic and has reduced side effects.